Eufimisme dan Desfemisme Sebagai Bentuk Performa Kritik Sosial-Politik pada Kolom Sunday Meme Jawa Pos Edisi Oktober 2015-Mei 2016 dan Implikasinya dalam Pelajaran Bahasa Indonesia Smp Kelas VIII - Utami, Rika Putri, Dra. Atiqa Sabardila, M.Hum (2016)
This study aimed to describe the forms of euphemisms and dysphemisms, references of euphemism and dysphemisms, and functions of euphemisms and dysphemisms in Sunday Meme column of Jawa Pos, and the implication in Indonesian Language Learning. Method of profiding data using techniques involved free refer conversation (SLBC) and technical notes. Data analysis using Agih and Padan. The results of research there are sixteen forms of euphemisms in Sunday Meme column, those form are figurative expressions, one word to replace another word, loan words, foreign technical term using, abbreviation, apofisis, remodeling, acronym, flippancy, periphrase, general form to spesific form, irony, personification, hyperbole, prolapsis, and pun or paronomasia. The forms of dysphemisms in Sunday Meme column including one word to replace another word, figurative expressions, clipping, and foreign technical term using. Euphemisms's Reference in Sunday Meme column including phenomena, characteristic and condition, activity, noun, person, and profession. Reference of dysphemisms in Sunday Meme column including activity, characteristic and condition, profession, and phenomena. The functions of euphemisms are to tease or criticize other smoothly, make a statement softly, to disguise a meaning, to replace forbidden words, taboos, vulgar or negative imaged word. Reference of dysphemisms in Sunday Meme column are to give negative description, show one's dislike or disagreement, explain forbidden words, taboos, vulgar on negatif imaged words, and sacrilege or criticize about someone ore something. This research could also be implied as media or teaching materials to write a news in Indonesian language learning for junior high school.